Kinematic Analysis of Parallel Manipulators by Algebraic Screw Theory - Gallardo-Alvarado, Jaime; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book reviews the fundamentals of screw theory concerned with velocity analysis of rigid-bodies, confirmed with detailed and explicit proofs. The author additionally investigates acceleration, jerk, and hyper-jerk analyses of rigid-bodies following the trend of the velocity analysis. With the material provided in this book, readers can extend the theory of screws into the kinematics of optional order of rigid-bodies. Illustrative examples and exercises to reinforce learning are provided. Of particular note, the kinematics of emblematic parallel manipulators, such as the Delta robot as well as the original Gough and Stewart platforms are revisited applying, in addition to the theory of screws, new methods devoted to simplify the corresponding forward-displacement analysis, a challenging task for most parallel manipulators. Stands as the only book devoted to the acceleration, jerk and hyper-jerk (snap) analyses of rigid-body by means of screw theory; Provides new strategies to simplify the forward kinematics of parallel manipulators that can be easily implemented by non-experts in robot kinematics; Provides readers the opportunity to extend the theory of screws into the desired order of kinematic analysis in approaching open problems, e.g. the correct characterization of singularities in closed kinematic chains; Includes numerous end of chapter problems and solutions to illustrate concepts presented.
Part 1. General Introduction -- An Overview of the Theory of Screws -- An Overview of Parallel Manipulators -- Part 2. Fundamentals of the Theory of Screws -- Mathematical Background -- Velocity Analysis -- Part 3. Higher-Order Kinematic Analyses of Rigid Body -- Acceleration Analysis -- Jerk Analysis -- Hyper-Jerk Analysis -- Part 4. Kinematics of Parallel Manipulators by Means of Screw Theory Exemplified -- 3R2T Parallel Manipulator -- Two-Degrees-of-Freedom Parallel Wrist -- 3-RRPS Parallel Manipulator -- 3RRRS+3RRPS Parallel Manipulator -- Part 5. Emblematic Parallel Manipulators -- Tyre Testing Machine of Gough -- The Original Stewart Platform -- Delta Robot -- Appendix A: Full Answers to Selected Exercises -- Appendix B: A Simple Method to Compute the Rotation Matrix -- Appendix C: Computer Codes -- Appendix D: Animations of Novel Parallel Manipulators.
Keywords: Machinery; Control engineering; Robotics; Automation; Mechanics, Applied; Solids; Machinery and Machine Elements; Control, Robotics, Automation; Solid Mechanics